The transition of care from fertility specialists to obstetricians: maternal adjustment and postpartum depressive symptoms. (January 2013) - Darwiche, Joëlle; Maillard, Florine; Germond, Marc; Favez, Nicolas; Lancastle, Deborah; de Roten, Yves; Guex, Patrice; Despland, Jean-Nicolas
Aim: This study examines the transition from fertility to obstetrical care of women who conceived through IVF.Materials & methods: 33 women filled out questionnaires before IVF, during pregnancy and after birth on infertility stress, maternal adjustment and depressive symptoms. During pregnancy, they participated in an interview about their emotional experiences regarding the transition. Responses were sorted into three categories: Autonomy, Dependence and Avoidance.Results: Exploratory results show that 51.5% of women had no difficulties making the transition (Autonomy), 21.2% had become dependent (Dependence) and 27.3% had distanced themselves from the specialists (Avoidance). Women who became dependent had more trouble adjusting to motherhood and more depressive symptoms.Conclusion: Difficulty making the transition may be linked to decreased ability to adjust to motherhood and more postpartum depressive symptoms.